Polymorphisms of base-excision repair genes and the hepatocarcinogenesis - Mattar, Manar-Aleslam M.; Zekri, Abdel-Rahman N.; Hussein, Nehal; Morsy, Heba; Esmat, Gamal; Amin, Magdy A. (Gene, 2018)
To determine the possible association between polymorphisms of DNA repair genes, including XRCC1 Arg194Tryp, Arg280His, and Arg399Glu, APE1 Asp148Glu, and NEIL2 Arg257Leu, and the risk of developing hepatitis C virus (HCV)-related hepatocellular carcinoma (HCC). A total of 264 subjects were recruited in this retrospective case-control study and were categorized into four groups: 88 control subjects (CR), 53 chronic hepatitis C patients (CHC), 36 liver cirrhotic patients (LC), and 87 HCC patients. The XRCC1 Arg194Tryp, Arg280His, and Arg399Glu polymorphisms were detected using PCR-RFLP, while real-time PCR was used to genotype APE1 Asp148Glu and NEIL2 Arg257Leu. Our data revealed that, compared with the healthy controls, for those subjects with the XRCC1 Arg194Trp genotype, the risk of developing CHC, LC, and HCC was increased by 6.66- (odds ratio (OR) = 6.667; 95% confidence interval (CI) = 3.244–13.701; P > 0.01), 3.85- (OR = 3.852; 95% CI = 1.797–8.256; P > 0.01), and 2.14-fold (OR = 2.14; 95% CI = 1.13–4.06; P > 0.05), respectively. There was no association between the risk of HCC development and the XRCC1 Arg280His or XRCC1 Arg399Gln genotypes. Moreover, the analysis showed a lack of association between APE1 Asp148Glu and the risk of HCC development. The analysis of clinicopathological parameters showed that the HCC patients with the XRCC1 Arg280His polymorphism were 2.9 fold more likely to have hepatic lesions in both hepatic lobes (OR: 2.9; 95% CI: 1.15–7.29). Notably, in the HCC patients, the prevalence of the APE1 polymorphism in the males was four times higher than that in the females (OR = 4; 95% CI = 1.129–14.175; P > 0.05). Our results indicate that the XRCC1 Arg194Trp polymorphism could be a risk factor for HCV-related HCC development in Egypt. •XRCC1 Arg194Trp genotype may increase the risk of HCV related liver disease.•No association of XRCC1 codons 280,399 or APE1 codon148 with HCC risk.•NEIL2 Arg257Arg wild-type genotype is present in the Egyptian population.